Stereoselective Copper‐Catalyzed Direct Aldol Reaction of β, γ‐Unsaturated α‐Ketoesters with Coumaran‐3‐Ones. Issue 2 (27th October 2020) - Li, Kuiliang; Sun, Xiang; Li, Linge; Zha, Zhenggen; Zhang, Feng‐Lian; Wang, Zhiyong
Abstract: An efficient direct aldol reaction between coumaran‐3‐ones and β, γ‐unsaturated α‐ketoesters by virtue of a chiral copper complex is developed. A series of coumaran‐3‐one derivatives containing chiral tertiary alcohol structures are obtained in excellent yields and stereoselectivities. Abstract : An efficient direct aldol reaction between coumaran‐3‐ones and β, γ‐unsaturated α‐ketoesters by virtue of a chiral copper complex is reported, affording the coumaran‐3‐one derivatives containing chiral tertiary alcohol structures with an excellent enantioselectivity (up to 95/96 % ee ) and high yield (up to 96 %). The configuration of the product 3 a was identified by single X‐ray. Scaling up the reaction to gram quantities, the desired product 3 a could be obtained with a good yield (90 %) and a great ee value (92/95 %). Notably, the aldol products are rich in functionalities, offering great latitude for further structural elaborations of biologically important chiral coumaran‐3‐one derivatives.